2018
DOI: 10.18203/2320-1770.ijrcog20180151
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of intrauterine adhesion management at a Nigerian tertiary hospital: a five-year review

Abstract: Background: Intrauterine adhesion is a cause of menstrual abnormalities and infertility, which are leading complaints in gynaecological practice in Nigeria. Determining the aetiology and management option would help reduce this problem. The objective of this study was to determine the aetiology, mode of presentation, management option and outcome of intrauterine adhesionsMethods: A retrospective analysis of intrauterine adhesions at the University of Abuja Teaching Hospital over a five-year period from 2012 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The prevalence of Asherman's syndrome of 5.3% found in this study is similar to that found in Uyo, Southwestern Nigeria, higher than the 1.6% reported from Abuja and 1.4% reported from Kano but lower than 29.2% reported from Lagos Southern Nigeria. 3,4,6,13 This is the most reproductively active age group and the majority of the patients (94.5%) were married. They are therefore more likely to be pregnant and develop a pregnancy complication like abortions that can result in uterine evacuations which is a common cause of AS.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The prevalence of Asherman's syndrome of 5.3% found in this study is similar to that found in Uyo, Southwestern Nigeria, higher than the 1.6% reported from Abuja and 1.4% reported from Kano but lower than 29.2% reported from Lagos Southern Nigeria. 3,4,6,13 This is the most reproductively active age group and the majority of the patients (94.5%) were married. They are therefore more likely to be pregnant and develop a pregnancy complication like abortions that can result in uterine evacuations which is a common cause of AS.…”
Section: Discussionmentioning
confidence: 98%
“…The commonest risk factor for the development of AS in this study was D&C. This was similar to the reports of other studies. 3,6,7,9 Endometrial injury induces ischemia and inflammatory reactions that lead to hypoxic cellular modifications and release of active substances leading to fibrosis and D&C is traumatic to the endometrium. 14,15 The other risk factors identified including myomectomy and caesarean sections may have operated through the same trauma to the endometrium that can occur during these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations